STRUKTUR SKELETON DAN OTOT ALAT GERAK SERTA MEKANISME GERAK IKAN AMFIBI Periophthalmus gracilis Eggert (MUDSKIPPER) DAN Andamia heteroptera Bleeker (ROCKSKIPPER) - , Gatot Nugroho Susanto, Prof. Dr. Nyoman Puniawati Soesilo, S.U ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Research on the comparison of skeleton, appendicular muscles, and locomotion between two amphibious fishes namely Periophthalmus gracilis and Andamia heteroptera was conducted. This comparison aims to determine structural and functional adaptation of these two fishes on each of its habitat. Fish specimens were taken from Siung and Drini beach, Gunungkidul, Yogyakarta. Skeleton preparation was prepared by alizarin red alcian blue staining method and appendicular muscles were prepared by using formalin-alcohol (1:1 v/v) solution. The result showed that a stronger and sturdier pectoral girdle with two layers of musculus abductor superficialis is observed in P. gracilis while the weaker one with two layers of musculus adductor superficialis is in A. heteroptera. Cube-like os basipterygium with branched lepidotrichia is observed in P. gracilis while the triangular-like one is observe in A. heteroptera. Caudal fin skeleton of P. gracilis are consist of eight os preural centrum with branched lepidotrichia while in A. heteroptera consist only four os preural centrum with no branched lepidotrichia. Presence of musculus interradialis pectoralis and musculus hypochordal longitudinalis are observed in P. gracilis while the same structure are absent from A. heteroptera. Therefore it can be concluded that P. gracilis have a lot of fusion between the skeleton so it can be used as an attached to complex appendicular muscle that are adapted to muddy environment. Andamia heteroptera utilizing rocks slippery conditions to assist the movement so that there are a lot of modifications and rare fusion of the skeleton. Appendicular muscles A.heteroptera simpler than P.gracilis.